Relational technologies as instruments of care in the Family Health Strategy - Tatiana Fernandes Kerches de Abreu; Fernanda Amendola; Monica Martins Trovo
ABSTRACT Objective: This article aims to identify the relational technologies used by Family Health Strategy nurses in their daily work when treating patients. Method: Descriptive and cross-sectional study with qualitative approach; conducted between May and July 2015, in three Basic Health Units of the Southern Region of the Municipality of São Paulo, with 19 nurses of the Family Health Strategy. Data were collected through a semi-structured interview, and the speeches were fully transcribed and analyzed according to the technique of content analysis. Results: From the speeches of the participants, three categories emerged, showing the unawareness of the concept, but the valorization of its use; which are the relational technologies used by the participating nurses (communication, listening, empathy and welcoming reception), as well as the report of barriers to the use of relational technologies. Final consideration: Although the nurses value the use of relational technologies, the participants denoted unawareness of the nomenclature and its associated concepts, suggesting superficiality in the understanding and use of these instruments in the context of care in the Family Health Strategy.